Political Economy of Infrastructure Spending in India - Khemani, Stuti (2012)
This paper examines a puzzle in the political economy of infrastructure in India -- the co-existence of relatively low shares of capital spending in public budgets alongside evidence of large demand for village infrastructure from poor voters. It argues that this pattern is due to infrastructure projects being used at the margin for political rent-seeking, while spending on employment and welfare transfers are the preferred vehicles to win votes for re-election. New suggestive evidence on the variation of public spending composition across states, and within states over time is offered that is consistent with this argument. This evidence underscores a growing argument in the development literature that the level and composition of public spending per se may not be sufficient metrics to assess the quality of public goods policies -- greater infrastructure spending in some contexts may go to political rents rather than to the actual delivery of broad public goods for growth and poverty reduction.